Level of noise pollution at different locations in Tangail municipal area, Bangladesh - Hoque, MMM; Basak, LK; Rokanuzzaman, M; Roy, Sajal (Bangladesh Journal of Scientific Research, 2014)
The study was carried out to ascertain the level of noise pollution at different locations in Tangail municipal area. For this purpose noise levels were measured at different locations at different periods of the day. At all the locations the level of noise were found to be higher than the acceptable level. The intensity of noise was found lower with increasing distance from the road side. The noise level on the main road near hospital, shopping center and bazars was above the standard level recommended by MoEF. From the survey motor vehicles were found as the main cause of high noise level. The most common problems with high noise level were found to increased heart beat, drowsiness, headache and hearing impairment. DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20228 Bangladesh J. Sci. Res. 26(1-2): 29-36, December-2013